2007
DOI: 10.1111/j.1551-2916.2007.01533.x
|View full text |Cite
|
Sign up to set email alerts
|

PMN–PT Ceramics Prepared By Spark Plasma Sintering

Abstract: (1−x)Pb(Mg1/2Nb2/3)O3−xPbTiO3 (PMN–PT) ceramics of stoichiometric composition were fabricated by conventional pressureless sintering (CS) and spark plasma sintering (SPS). The CS ceramics exhibited a change from relaxor to normal ferroelectric behavior (FE) with increasing PT content. However, low dielectric constants, frequency dispersion, and diffuse phase transition behavior typical for relaxors were obtained for all SPS ceramics. FE and piezoelectric measurements further demonstrated low remanent polarizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 46 publications
3
19
0
Order By: Relevance
“…[24] Due to the combined effects of PPT and nano-domain contribution as stated above, poled CZ5 ceramics exhibit superior piezoelectric performance at room temperature. The piezoelectric coefficient d 33 reached 357 pCN -1 , which is among the top values for randomly-orientated KNN ceramics and is comparable to those of hard PZT [25] 5 and PMN-PT [26] ceramics prepared by conventional route, though outperformed by PMN-PT crystals.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…[24] Due to the combined effects of PPT and nano-domain contribution as stated above, poled CZ5 ceramics exhibit superior piezoelectric performance at room temperature. The piezoelectric coefficient d 33 reached 357 pCN -1 , which is among the top values for randomly-orientated KNN ceramics and is comparable to those of hard PZT [25] 5 and PMN-PT [26] ceramics prepared by conventional route, though outperformed by PMN-PT crystals.…”
Section: Resultsmentioning
confidence: 79%
“…[24] Due to the combined effects of PPT and nano-domain contribution as stated above, poled CZ5 ceramics exhibit superior piezoelectric performance at room temperature. The piezoelectric coefficient d 33 reached 357 pCN -1 , which is among the top values for randomly-orientated KNN ceramics and is comparable to those of hard PZT [25] 5 and PMN-PT [26] ceramics prepared by conventional route, though outperformed by PMN-PT crystals.[27] Large unipolar strain output of 0.16 % was also obtained under an electric field of 6 kVmm -1 , accompanied by a small strain hysteresis (see Figure 1(c)), enabling the current material to be a promising potential for actuator applications. Nevertheless, excellent thermal stability of strain behavior is further demanded for successful implementations.…”
mentioning
confidence: 88%
“…Micrographs of the polished surfaces of 0.9NaNbO 3 -0.1SrTiO 3 ceramics processed by different means: a) conventionally sintered at 1 100 8C for 2 h (optical micrographs), and, b) SPS at 1 100 8C/50 MPa (scanning electron micrographs). [48] ADVANCED ENGINEERING MATERIALS 2009, 11 [129][130][131][132][133] The SPS process has also been determined to be very effective for the densification of 0.65Pb(Mg 1/3 -Nb 2/3 )O 3 -0.35PbTiO 3 ceramics. This fact is very important because, in this material, the higher the density and the larger the average grain size, the better the dielectric and piezoelectric properties that are obtained.…”
Section: High-sensitivity Piezoelectrics Chemically Derived From Pbtiomentioning
confidence: 99%
“…Moreover, the SPS process allows a capillary driven 0.65PMN-0.35PT single crystal to be fabricated, with a high density, by increasing the density of the polycrystalline matrix precursor during heat treatment. [131] Very recently, a deeper study, carried out by Zuo et al, [132] showed that a strongly frequency dependent and broad diffuse phase transition can be observed for all SPS samples, together with low remnant polarization and strain, and a high coercive field. These exceptional electrical properties of SPS samples are attributed to the fine grain size and the heterogeneity in microstructure and composition.…”
Section: High-sensitivity Piezoelectrics Chemically Derived From Pbtiomentioning
confidence: 99%
“…In this group, which shows piezoelectric effect, ten point groups (including 1, 2, m, mm2, 4, 4mm, 3, 3m, 6 and 6mm) have only one unique direction axis. Such crystals are polar crystals and they show spontaneous polarization and ferroelectric effect [20]. The particle size is calculated from X-ray diffraction profiles of strong reflections with intensity % greater than 30 using Scherrer's equation by measuring the full width at half maximum (FWHM).…”
Section: X-ray Analysis Of Bnnmentioning
confidence: 99%